Perception on the general competences of the nursing teachers of the intensive care area. Hospital Guillermo Almenara Irigoyen, 2018: Percepción sobre las competencias generales de los docentes de enfermería del área de cuidados intensivos, Hospital Guillermo Almenara Irigoyen, 2018. - Alva-Mayuri, Carmen Susana (2019)
Objective: To determine the perception on the general competences of nursing teachers by specialist nurses in the intensive care area at the Guillermo Almenara Irigoyen Hospital in 2018. Key words: general competences, nurse, intensive care. Methods: Prospective study and design with qualitative-quantitative approach. Thirty-eight nurses were surveyed using a general skills perception scale, and 7 nurses were interviewed with an interview guide, all intensive care specialists. The perception was categorized into good, fair and bad. Descriptive statistics was used, using absolute and relative frequencies, as well as mean and standard deviation. Results: The average age was 41.39 ± 7.92 years, 92.1% being female. The general competencies of nursing teachers in the intensive care area reached a regular perception of 55.3% and good perception in 44.7%. The aspects with the highest degree of agreement were adaptation to the different situations that occur in daily practice (65.8%), the empathy shown to students (57.9%) and the ability to solve emergency problems (50%). The years of experience were the most relevant referred to the adequate capacity and execution of the nurses. Conclusion: The perception about the general competences of the nursing teachers of the intensive care area of the Guillermo Almenara Irigoyen Hospital in the year 2018 was regular.